Depressive symptoms, excessive reassurance seeking, and relationship maintenance. (February 2017) - Fowler, Craig; Gasiorek, Jessica
Using a sample of 143 heterosexual, ethnically diverse couples, we explored the consequences of individuals' depressive symptomology and excessive reassurance seeking (ERS) for (a) the efforts they and their partners make to maintain their relationship and (b) the satisfaction reported by each relational party. Data were analyzed using an extension of the actor–partner interdependence model. We found actor effects of depression on satisfaction and on relationship maintenance behavior. We also detected significant actor effects of ERS on relationship maintenance behavior. There was inconsistent evidence of partner effects and of the predicted indirect effects. Results suggest that depression and the tendency to engage in ERS may exert countervailing influences on the enactment of relationship maintenance: For both men and women, depression was a negative predictor of self-reported relationship maintenance, whereas ERS was a positive predictor. We suggest that ERS could be considered a form of relationship maintenance in its own right.